2009
DOI: 10.4161/cbt.8.13.8631
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial electron transport chain blockers enhance 2-deoxy-D-glucose induced oxidative stress and cell killing in human colon carcinoma cells

Abstract: Increasing evidence suggests that cancer cells (relative to normal cells) have altered mitochondrial electron transport chains (ETC) that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 47 publications
3
56
0
Order By: Relevance
“…Mimicking glucose deprivation, 2DG potently induces mitochondrial oxidative stress [36]. The phosphorylated product of 2DG, 2DG-6-P, can only undergo the first enzymatic reaction in the PPP by glucose-6-phosphate dehydrogenase (G-6-PD) to regenerate one molecule of NADPH from NADP+, but the product 2-Deoxy-D-glucose-6-phosphoglaconalactone cannot be further metabolized to generate the second molecule of NADPH [49,54]. In general, treatment with 2DG results in pyruvate and NADPH deficiencies, damaging the antioxidant defenses of cancer cells and may render them more vulnerable to oxidative stress induced by radiotherapy or chemotherapy.…”
Section: Inhibition Of Antioxidationmentioning
confidence: 99%
“…Mimicking glucose deprivation, 2DG potently induces mitochondrial oxidative stress [36]. The phosphorylated product of 2DG, 2DG-6-P, can only undergo the first enzymatic reaction in the PPP by glucose-6-phosphate dehydrogenase (G-6-PD) to regenerate one molecule of NADPH from NADP+, but the product 2-Deoxy-D-glucose-6-phosphoglaconalactone cannot be further metabolized to generate the second molecule of NADPH [49,54]. In general, treatment with 2DG results in pyruvate and NADPH deficiencies, damaging the antioxidant defenses of cancer cells and may render them more vulnerable to oxidative stress induced by radiotherapy or chemotherapy.…”
Section: Inhibition Of Antioxidationmentioning
confidence: 99%
“…A natural possibility would be to concurrently inhibit the mitochondria themselves through the use of electron transport chain decouplers such as antimycin A or rotenone. It has previously been shown that the combination of 2DG and these compounds makes cells more sensitive to 2DG by increasing ROS, as glucose may act as an inhibitor of ROS production, and decreasing available NADPH in the pentose phosphate shunt [41,42]. Increased ROS may be exploited through radiation therapy in conjunction with 2DG as previously described [32].…”
Section: Discussionmentioning
confidence: 92%
“…These specific manipulations may serve as a model for radio-sensitizing tumor cells [24,27]. A possible therapeutic approach of targeting metabolic pathways with 2DG is currently used in several clinical trials (phase I/II) in different solid tumors [28].…”
Section: Radio-sensitivity Is Enhanced By Metabolic Inhibitors In Igrmentioning
confidence: 99%
“…Oxidative stress caused by increased ROS generation seems to be a common feature of cancer cells, at least in part due to respiratory chain malfunction [22,23]. This makes cancer cells more vulnerable to damage by additional ROS, either through inhibiting ROS scavenger systems or through enhancing ROS generation [24][25][26]. As both cell lines maintained their metabolic and proteomic phenotype, even as Fig.…”
Section: Radio-sensitivity Is Enhanced By Metabolic Inhibitors In Igrmentioning
confidence: 99%